2023
DOI: 10.1093/hropen/hoad014
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix-derived scaffolds in constructing artificial ovaries for ovarian failure: a systematic methodological review

Abstract: STUDY QUESTION What is the current state-of-the-art methodology assessing decellularized extracellular matrix (dECM)-based artificial ovaries for treating ovarian failure? SUMMARY ANSWER Preclinical studies have demonstrated that decellularized scaffolds support the growth of ovarian somatic cells and follicles both in vitro and in vivo. WHAT IS KNOWN ALREADY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
(157 reference statements)
0
0
0
Order By: Relevance
“…The main problem of decellularized OT matrix is the variable size of preantral follicles (30-150 µm), making them hardly adaptable to the pores of the matrix. One alternative is to transform this matrix into a thermosensitive hydrogel, an approach that allows perfect encapsulation of isolated follicles, while retaining the composition of the matrix: in vitro experiments using this procedure demonstrated that isolated mouse preantral follicles could successfully survive in decellularized OT [76,77]. Some studies demonstrated increased estradiol (E2) or progesterone (P4) compared to fresh ovaries in vitro [78,79] whereas others observed that follicular development and ovarian function of decellularized-based artificial ovaries contributed to higher E2 or P4 or inhibin A compared with those in ovariectomized mice, also in vivo [72,74,80].…”
Section: In Vitro Maturation Of Isolated Ovarian Stem Cells (Oscs)mentioning
confidence: 99%
“…The main problem of decellularized OT matrix is the variable size of preantral follicles (30-150 µm), making them hardly adaptable to the pores of the matrix. One alternative is to transform this matrix into a thermosensitive hydrogel, an approach that allows perfect encapsulation of isolated follicles, while retaining the composition of the matrix: in vitro experiments using this procedure demonstrated that isolated mouse preantral follicles could successfully survive in decellularized OT [76,77]. Some studies demonstrated increased estradiol (E2) or progesterone (P4) compared to fresh ovaries in vitro [78,79] whereas others observed that follicular development and ovarian function of decellularized-based artificial ovaries contributed to higher E2 or P4 or inhibin A compared with those in ovariectomized mice, also in vivo [72,74,80].…”
Section: In Vitro Maturation Of Isolated Ovarian Stem Cells (Oscs)mentioning
confidence: 99%